Fatigue life and resistance analysis of COG assemblies under hygrothermal aging. Issue 3 (February 2015) - Zhang, Wenguo; Ma, Jianhua; Gao, Lilan; Zhang, Zhe; Gao, Hong
Highlights: The coupling loads of temperature–electric–hygrothermal stress for COG assembly were built. Different hygrothermal aging time seriously influences the relative resistance change. Fatigue life decreases with aging time under loads of temperature–electric–hygrothermal stress. The relation of hygrothermal aging time and the damage factor was obtained. Abstract: The present work deals with studying fatigue life and electrical properties of chip-on-glass (COG) assemblies undergoing the coupling loads of temperature, electrical current and hygrothermal stress by shear fatigue tests. Firstly, as the COG assemblies are exposed in hygrothermal environment, an increased hygrothermal aging time leads to an increased relative resistance of COG assemblies. Secondly, during the fatigue experiments, the fatigue life of COG assemblies decreases with an increase of hygrothermal aging time. The change of relative resistance displays different trends under different aging degrees. When the hygrothermal aging time is less than 96 h, the relative resistance increases rapidly in the initial stage, then the rate of rise decreases subsequently, and finally the relative resistance falls to a stable value suddenly. By contrast, the relative resistance of COG assemblies having more than 168 h hygrothermal aging increases rapidly with increasing fatigue cycles. Owing to the effects of hygrothermal aging and fatigue on the change of assemblies' resistance, the total of relative resistance increases with increasing hygrothermal aging time. Finally, the hygrothermal aging damage defined as life reduction after degradation aggravates exponentially with aging time on the basis of the Miner's linear damage rule. The fatigue life prediction model based on the Miner's linear damage rule and the Basquin's equation is proposed and yielded to good prediction for the COG assemblies undergoing hygrothermal aging.